2006
DOI: 10.1007/s10439-006-9223-4
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Element Stress Analysis of a Multicomponent Model of Sheared and Focally-Adhered Endothelial Cells

Abstract: Hemodynamic forces applied at the apical surface of vascular endothelial cells may be redistributed to and amplified at remote intracellular organelles and protein complexes where they are transduced to biochemical signals. In this study we sought to quantify the effects of cellular material inhomogeneities and discrete attachment points on intracellular stresses resulting from physiological fluid flow. Steady-state shear- and magnetic bead-induced stress, strain, and displacement distributions were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 60 publications
4
39
0
Order By: Relevance
“…Poisson's ratio of membrane, cytoplasm, and nucleus was set at 0.33 [27]. Normally, the elastic modulus of the cytoplasm is only one-quarter that of the nucleus [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poisson's ratio of membrane, cytoplasm, and nucleus was set at 0.33 [27]. Normally, the elastic modulus of the cytoplasm is only one-quarter that of the nucleus [28].…”
Section: Methodsmentioning
confidence: 99%
“…The initial cellular density was assumed as 1000 kg/m 3 [31], and 1250 kg/m 3 was used as the density of cytoplasm, nucleus, and membrane in the endothelial cell [27]. Previously, the density of an osteoblast was assumed as 125 kg/m 3 [19], and, for osteocyte-like MLO-Y4 cell, 1500 kg/m 3 , 1800 kg/m 3 , and 600 kg/m 3 were set as the densities of cytoplasm, nucleus, and membrane, respectively [26].…”
Section: Methodsmentioning
confidence: 99%
“…They observed maximum displacement of approximately 400 nm at the apical side of the cell, under a uniform shear stress of 2 Pa. We applied a uniform shear stress with magnitude of 2 Pa over the surface of the EC monolayer and observed a maximum displacement of 400 nm over the surface of ECs (figure 2b). Furthermore, Ferko et al [23] developed a model of single EC with nucleus, cytosol and FAs, but not including the apical layer and cytoskeleton. They observed a maximum displacement of 30 nm at the apical side of the single EC when a uniform shear stress of 1 Pa was applied on the cell surface.…”
Section: Model Parametersmentioning
confidence: 99%
“…On the other hand, excluding the SFs from the EC model induces a dramatic decrease in stresses around the nucleus. Ferko et al [23] reported the stress amplification of three-to four-fold around the nucleus in their single cell model where a uniform shear stress of 1 Pa was applied on the surface of the EC. The stresses over the nucleus in our one EC model (results not shown), exposed to a uniform shear stress of 1 Pa, are in the same range of stresses observed by Ferko et al [23].…”
Section: Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation